30 years of rabies vaccination with Rabipur: a summary of clinical data and global experience. (March 2015) - Giesen, Alexandra; Gniel, Dieter; Malerczyk, Claudius
Abstract : Rabies poses a threat to more than 3.3 billion people worldwide and is estimated to cause about 60, 000 deaths a year. However, according to the WHO, it is still one of the most neglected diseases in developing countries. Human rabies vaccinations are critical components of pre-exposure and post-exposure prophylaxis. Rabipur, the first purified chick embryo cell-culture vaccine, was licensed in Germany in 1984, and later in more than 60 countries worldwide. The immunogenicity, efficacy and safety of Rabipur have been assessed in numerous clinical trials in pre- and post-exposure regimens, using both intramuscular and intradermal routes of administration. The trial populations have involved adults and children, including healthy volunteers and individuals bitten by laboratory-proven rabid animals, malnourished children and immunocompromised individuals. Extensive, worldwide clinical experience with Rabipur over the past 30 years has shown the vaccine to be immunogenic, effective and generally well tolerated.